2011
DOI: 10.1002/art.30512
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: Results of an international multicenter collaborative study

Abstract: Objective Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ~40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 265 publications
(213 citation statements)
references
References 18 publications
8
194
0
11
Order By: Relevance
“…Furthermore, MWS mutations are often associated with hearing loss, which presents later in life than in NOMID patients (18,21). Somatic mosaicism for NLRP3 mutations is observed in some sporadic cases of NOMID, as well as the closely related autoinflammatory disorder Schnitzler syndrome (22), but is rarely associated with the other milder phenotypes (23,24).…”
Section: Significancementioning
confidence: 99%
“…Furthermore, MWS mutations are often associated with hearing loss, which presents later in life than in NOMID patients (18,21). Somatic mosaicism for NLRP3 mutations is observed in some sporadic cases of NOMID, as well as the closely related autoinflammatory disorder Schnitzler syndrome (22), but is rarely associated with the other milder phenotypes (23,24).…”
Section: Significancementioning
confidence: 99%
“…Большинство мутаций являются миссенс-мутациями и наследуются по аутосомно-доми-нантному типу. Однако в случае синдрома CINCA/NOMID обнаруживается большой процент спорадических мута-ций в гене NLRP3 [17], а также встречаются случаи соматического мозаицизма [18,19]. Кроме того, в ряде работ показано, что пациенты с клинической картиной CINCA/NOMID могут иметь мутации вне области гена NLRP3, кодирующей NOD-домен NLRP3-инфламмасомы, или вообще в другом гене (NLRP12) [20].…”
Section: Discussionunclassified
“…The role of NLRP3 gene polymorphism remains unclear (34). In 2011, Tanaka et al reported somatic NLRP3 gene mosaicism in 18 of 26 previously mutationnegative CINCA patients, emphasizing the limitations of genetic testing in MWS (35).…”
Section: Discussionmentioning
confidence: 99%